A presença do currículo oculto no Currículo Paulista na área de Ciências da Natureza: possibilidades de superação a partir da perspectiva crítica freireana - Bimbatti, Bianca Rita (2024)
The curriculum is historically understood by an organizational perspective in relation to content. However, scientific production in the area and the practice experienced in schools shows that the curriculum is configured far beyond technical planning, involving political, ethical and aesthetic aspects. Furthermore, the curriculum is configured as a space for the production of meanings, imposing values and behaviors on its students. In this sense, Apple (2006) established a relationship between the organization of the educational system and the capitalist economic system, reflecting on the existence of a hidden curriculum in schools. This hidden curriculum is responsible for guaranteeing the relevant social learning necessary for the maintenance of the hegemonically dominant classes in the capitalist economic system. In this work, an analysis of the Natural Sciences area of the São Paulo Curriculum was carried out, in order to find aspects of the curriculum hidden in the contents selected for the discipline, and thus finding possibilities for overcoming them using Freire's critical pedagogy. Based on a documentary analysis and semistructured interviews with professors in the area of Natural Sciences, two categories of analysis were defined to carry out this work: ideology and authentic praxis, based on the epistemological contributions of Paulo Freire. During the research, it was possible to highlight the Paulista Curriculum as an ideological document, which contributes to an instrumentalized and decontextualized Science Teaching, functioning as an adaptation tool.